The illnesses of Herod the Great - Francois P. Retief; Louise Cilliers (Acta Theologica)
Herod the Great, Idumean by birth, was king of the Jews from 40BC to AD 4. An able statesman, builder and warrior, he ruthlessly stamped out all perceived opposition to his rule. His last decade was characterised by vicious strife within his family and progressive ill health. We review the nature of his illnesses and suggest that he had meningoencephalitis in 59 BC, and that he died primarily of uraemia and hypertensive heart failure, but accept diabetes mellitus as a possible underlying etiological factor. The possibility that Josephus’s classical description of Herod’s disease could be biased by “topos” biography (popular at the time), is discussed. The latter consideration is particularly relevant in determining the significance of the king’s reputed worminfested genital lesions.